2018
DOI: 10.29252/aassjournal.6.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Are Heart Muscle Irisin Levels and FNDC5 Gene Expression Regulated by Endurance and Resistance Exercises?

Abstract: Background. Irisin is the result of the proteolysis of fibronectin type III domain-containing protein 5, the levels of which are determined by physical activity. Objective(s). This study aims to identify changes in FNDC5 gene expression and the heart muscle irisin levels in male rats following 8 weeks resistance and endurance trainings. Methods. Fifteen male rats (10-12 weeks old and 331.8±63.09 g in weight) were randomly assigned to three groups: control, resistance and endurance training groups (5 in each gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Exercise is a strong stimulator for the production of FNDC5/ irisin in cardiac tissue (130)(131)(132), and the exercise-induced changes in irisin are associated with heart diseases (10,133). Aydin et al reported that irisin is highly presented in myocardium of both sedentary and exercise young rats, and it increased particularly in the connective tissues of heart after acute exercise (134).…”
Section: Fndc5/irisin-pink1/pakin-lc3ii/i-p62 Pathway In Exercise And...mentioning
confidence: 99%
“…Exercise is a strong stimulator for the production of FNDC5/ irisin in cardiac tissue (130)(131)(132), and the exercise-induced changes in irisin are associated with heart diseases (10,133). Aydin et al reported that irisin is highly presented in myocardium of both sedentary and exercise young rats, and it increased particularly in the connective tissues of heart after acute exercise (134).…”
Section: Fndc5/irisin-pink1/pakin-lc3ii/i-p62 Pathway In Exercise And...mentioning
confidence: 99%